1995
DOI: 10.1254/jjp.68.65
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1A-Receptor Subtype Mediates the Effect of Fluvoxamine, a Selective Serotonin Reuptake Inhibitor, on Marble-Burying Behavior in Mice

Abstract: ABSTRACT-The effect of fluvoxamine, a selective serotonin (5-HT) reuptake inhibitor, was studied in a model of anxiety and/or obsessive compulsive disorder (OCD) in mice. In the anxiety/OCD model, marbleburying behavior, marble-burying was significantly suppressed by fluvoxamine at 30 and 60 mg/kg, p.o. and the monoamine reuptake inhibitor clomipramine, at 60 mg/kg, p.o. No suppressive effect, however, was observed by the selective norepinephrine reuptake inhibitor desipramine at doses from 15 to 60 mg/kg, p.o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
110
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(123 citation statements)
references
References 12 publications
(9 reference statements)
11
110
1
1
Order By: Relevance
“…The similarity in effect seen between inactivation and blockade is in line with previous studies evaluating models of depression [7,13,35]. In both the forced swim test and the tail suspension test an antidepressant-like effect has been observed after inactivation of the 5-HT 7 receptor [7,13] and also after treatment with a selective antagonist [13,35].It has previously been found that agonism at the 5-HT 1A receptor also reduces marble burying behavior [19,23]. This is of interest in relation to previously described relationships between 5-HT 1A and 5-HT 7 receptors.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…The similarity in effect seen between inactivation and blockade is in line with previous studies evaluating models of depression [7,13,35]. In both the forced swim test and the tail suspension test an antidepressant-like effect has been observed after inactivation of the 5-HT 7 receptor [7,13] and also after treatment with a selective antagonist [13,35].It has previously been found that agonism at the 5-HT 1A receptor also reduces marble burying behavior [19,23]. This is of interest in relation to previously described relationships between 5-HT 1A and 5-HT 7 receptors.…”
supporting
confidence: 87%
“…Establishing good animal models for OCD has proved to be exceedingly difficult, most clearly demonstrated by the large number of models tried [21,23]. Marble burying is one of the more well-established models for OCD [19,27,28]. New models of supposedly stereotypic behavior, such as the screen chewing and head dipping tests used along with marble burying in the present study, are also continuously being developed and tested [2].…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Inhibition of object burying was originally suggested as a screening test for anxiolytic activity, but several studies in the last ten years led to the conclusion that marble-burying behavior does not model anxiety, but may rather be related to compulsive behaviors (Albelda and Joel, 2012). The predictability of the marbleburying test after acute drugs administration has been widely demonstrated in research articles (Gawali et al, 2016;Ichimaru et al, 1995;Joel, 2006;Kalariya et al, 2015). Thus, we decided to compare acute effects of atomoxetine on the marble-burying test with its chronic effects on patients with a primary diagnosis of hoarding disorder.…”
Section: Pre-clinical Investigationmentioning
confidence: 99%